Phenomenological Alternatives of the Lifeworld: Between Multiple Realities and Virtual Realities - Butnaru, Denisa (SocietàMutamentoPolitica, 2016)
The concept of “lifeworld” is of high importance in the phenomenological context as well as in the comprehensive sociological theory, continuing to animate contemporary debates. Given the recent development of what is known as ICT (information and communication technologies) and in particular of the virtual reality (VR), the lifeworld configurations changed. The aim of this paper is to show first how the concept of lifeworld has been modified by the presence of ICT and VR. Second it shall be stressed how such instances as subjectivity and intersubjectivity are challenged in their phenomenological consequences by such transformations. In a further step, the discussion of these aspects shall be correlated to the postphenomenological orientation.